Efficiency of neutralization of electric charges on the surface of dielectric nonwoven fabric of two dual and triode electrode systems - Yahiaoui, B.; Messaoudene, A.; Melahi, A.; Rahmani, A.; Bendahmane, B.; Dascalescu, L. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The accumulation of electrostatic charges are exploited in various technological and industrial applications, but they can also pose significant challenges, especially due to the accumulation in inappropriate locations that can reach dangerous levels. Problem. The static charges are often considered annoying and constitute one of the main sources of hazards. Thus, their neutralization is more than necessary. The objective of this work is to improve the neutralization rate with equipment that can be easily integrated in the production lines. Novelty. The paper reports a comparative study of the neutralization efficiency of two electrode systems, dual and triode, with different high alternating voltages at the industrial frequency of 50 Hz. The use of the industrial frequency of 50 Hz reduces the elements of the neutralization equipment. By connecting the grid to ground, we aim to impose a zero potential on the surface of the initially charged polypropylene fibrous dielectric and to determine the variation of the neutralization rate as a function of the discharge intensity (voltage amplitude). Methodology. The samples were charged during 10 s using a triode-type corona electrode configuration supplied by negative or positive DC high voltage. After 300 s of the charging process. The neutralization was performed during 4 s, using the dual or the triode systems powered by sinusoidal high voltage. Neutralization efficiency is achieved by non-contact sampling of surface potential profiles before and after neutralization. The results show that neutralization efficiency is proportionate to the discharge current intensity. The neutralization using the triode system is more efficient. The results show the possibility of imposing a desired potential on the charged or uncharged dielectric surface by acting on the potential of the metallic grid and the discharge intensity of the triode system. Practical value. The results demonstrate the proportionality of the neutralization efficiency with the discharge intensity for the triode system. Therefore, an adjustment of the voltage amplitude is necessary in order to optimize its efficiency for the dual system.

Накопичення електростатичних зарядів використовуються в різних технологічних та промислових застосуваннях, але вони також можуть становити значні проблеми, особливо через накопичення в невідповідних місцях, що може досягати небезпечних рівнів. Проблема полягає в тому, що статичні заряди часто вважаються неприємними і є однією з основних причин небезпек. Тому їх нейтралізація є більш ніж необхідною. Метою роботи є покращення рівня нейтралізації за допомогою обладнання, яке можна легко інтегрувати в виробничі лінії. Новизна. У статті представлено порівняльне дослідження ефективності нейтралізації двох електродних систем:діодної та тріодної, при різних високих змінних напругах на промисловій частоті 50 Гц. Використання промислової частоти 50 Гц зменшує кількість елементів нейтралізаційного обладнання. Підключення сітки до землі дозволяє нав’язати нульовий потенціал на поверхні початково зарядженого поліпропіленового волокнистого діелектрика та визначити зміну рівня нейтралізації залежно від інтенсивності розряду (амплітуди напруги). Методологія. Зразки заряджали протягом 10 с за допомогою електродної конфігурації типу тріода, живленої негативною або позитивною постійною високою напругою. Після 300 с заряджання, нейтралізація проводилась протягом 4 с за допомогою подвійних або тріодних систем, живлених синусоїдальною високою напругою. Ефективність нейтралізації визначалась шляхом безконтактного зняття профілів поверхневого потенціалу до та після нейтралізації. Результати показали, що ефективність нейтралізації пропорційна інтенсивності розрядного струму. Нейтралізація за допомогою тріодної системи є більш ефективною. Результати показують можливість нав’язати бажаний потенціал на зарядженій або незарядженій діелектричній поверхні, впливаючи на потенціал металевої сітки та інтенсивність розряду тріодної системи. Практична цінність. Результати демонструють пропорційність ефективності нейтралізації до інтенсивності розряду для тріодної системи. Тому коригування амплітуди напруги є необхідним для оптимізаціїїїефективності для подвійної системи.
Keywords: surface potential; corona discharge; charge neutralization; fibrous electrets; triode system; поверхневий потенціал; коронний розряд; нейтралізація зарядів; волокнисті електрети; тріодна система